Pengaruh Konflik dan Stress Kerja terhadap Kinerja Karyawan BPR X dengan Lingkungan Kerja Sebagai Variabel Intervening - Lela Dina Berliana; Ardian Adhiatma (CV. ULIL ALBAB CORP, 2025)
The purpose of writing this thesis proposal is to analyze the influence of work conflict and work environment variables on employee performance with work stress as the intervening variable. The method used in this research is a quantitative method where the population is all employees of BPR X with the sample calculated using the Slovin formula. From this writing, a hypothesis is obtained, namely that work conflict has a negative effect on employee performance at BPR X. The work environment has a positive effect on employee performance at BPR X. Work conflict has a positive effect on work stress at BPR X. The work environment has a negative effect on work stress at BPR X. Work stress has a negative effect on employee performance at BPR X. Job stress mediates the influence of work conflict on employee performance at BPR X. Job stress mediates the influence of the work environment on employee performance at BPR X.